Governmental Surveillance - The balance between security and privacy - Eneman, Marie (2020)
The increased digitalisation of society and recent developments in AI is laying the ground for surveillance capabilities of a magnitude we have not seen before. Surveillance can be conducted by several different actors in society, this project focuses on the Swedish police currently using a large ensemble of surveillance technologies. Earlier this year, significant legislative changes governing the police authorities use of digital surveillance were enacted. These changes mean that the police now have been given an extended mandate to use digital surveillance as part of their professional practice, which places demands on balanced decisions and informed responsibility. On the one hand, the police have an interest to use digital surveillance to increase efficiency and security in society; on the other hand, the police must balance their interests with citizen’s so-called integrity-interests and right to privacy. This study will therefore examine to what extent the Swedish Police Authority pay attention to questions such as integrity and privacy when introducing digital surveillance. The study is guided by the following questions: (i) What opportunities can be related to the implementation and use of digital surveillance in police work? (ii) What kind of challenges do the increasing use of digital surveillance create between organisational governance, police officers’ work practice, and the integrity of citizens - and how do the police tackle these challenges? Theoretically, we draw on the established research fields on surveillance and privacy and empirically this study is designed as a qualitative study of the Swedish Police as our main case